Konseling WhatsApp Gateway untuk Meningkatkan Kesiapsiagaan Masyarakat dalam Menghadapi Covid-19 - Riris Andriati; Fenita Purnama Sari Indah; Andiyan Andiyan; Marta Desri Ayu (Universitas Faletehan, 2021)
As of March 31, 2020, Indonesia reported 1,528 confirmed Covid-19 cases with 136 deaths and a case fatality rate (CFR) of 8.9%. Covid-19 pandemic limited activities, including the dissemination of information; thus, an intensive education was required to build community preparedness. The purpose of this study was to identify the effects of counseling through WhatsApp on the preparedness of Villa Pamulang Depok community in dealing with Covid-19. This study used an analytical quasi-experimental method and a one-group pretest-posttest design method. The samples of this study amounted to 44 people who were selected by proportional sample technique. The respondents received education via WhatsApp for 14 days. The effects of information dissemination through WhatsApp was measured by using paired sample t-test. The results of this study showed that there was a relationship between the spread of Covid-19 information via WhatsApp on the community preparedness at Villa Pamulang Depok in facing Covid-19 with p-value 0.004. The findings also showed the difference of Covid-19 preparedness before and after providing information about Covid-19 through WhatsApp. This research was expected to enrich knowledge of community preparedness as an effort of Covid-19 prevention.